Case report: Five patients with myocarditis after mRNA COVID-19 vaccination - Murase, Hiroki; Zhu, Yiqing; Sakaida, Keiya; Mizuno, Hayato; Mori, Hiromitsu; Iwayama, Hideyuki; Suzuki, Noriyuki; Nagai, Noriko; Okumura, Akihisa (Frontiers in Pediatrics, 2022)
Abstract Objectives: To describe clinical features and laboratory data of myocarditis after the mRNA COVID-19 vaccine in children. Methods: We reviewed patients younger than 18 years of age, who visited our hospital because of myocarditis within 1 week after BNT162b2 from June 2021 to January 2022. Results: We identified five male patients aged 12–16 years who presented to our hospital with myocarditis within 2–3 days after the second dose of BNT162b2 COVID-19 vaccination between June 2021 and January 2022. All patients experienced chest pain, and fever, pain other than chest pain, and shortness of breath were present in two, three, and two patients, respectively. The serum troponin I level was increased in all patients except one, and electrocardiogram (ECG) showed ST elevation in all patients. Echocardiography revealed pericardial effusion and decreased ejection fraction in three and one patients, respectively. In accordance with the Japanese guidelines for myocarditis, the patients were treated with colchicine and aspirin. Chest pain improved within a few days with no hemodynamic instability. The patients were discharged with no sequelae. Conclusions: ST changes on ECG and elevated troponin I levels may aid the diagnosis of myocarditis after mRNA COVID-19 vaccination